Laser cladding research for rail steel repair and reliability assessment - Subramaniam, N Alagu (Nanyang Technological University, 2022)
Rail failures due to excessive wear and other rail head defects is still predominant owing to the advanced railway systems with greater train traffic, higher train speed and axle load requirements. The sharp-radius curve tracks and crossing nose sections are especially susceptible to failures from extensive wear damage leading to significantly reduced service life. Regular maintenance and replacement of rails to address these failures will lead to lengthy queue for rail total replacement maintenance and high costs are incurred. Although premium rail steels and hardened rail heads can be considered as an alternative solution, it is not economically viable to replace the entire rail network using them. Hence laser cladding repair research was supported by the SMRT-NTU corporate lab project work. The objective of this research is to investigate laser cladding technique for rail steel repair and reliability assessment. The research objective is categorised and focused to address four main concerns with regards to adopting laser cladding for rail steel repair which include: 1) Laser cladding material process characterisation study, 2) Wear testing & analysis for durability study, 3) Shear testing & analysis for delamination study, and 4) On-track reliability studies by installing laser cladded test specimens on depot test track and mainline test trials. The present research direction involves a two-pronged approach. The first approach is to develop a strategy to research laser cladding experimental characterisation of rail steel and develop methodology for laser cladding repair and testing of localized rail head defects on critical rail components such as rails and crossing nose. The second involves pioneering research work to validate the durability and wear performance study as part of the SMRT-NTU research project on-track testing programme. XVI This is achieved by installing the laser cladded rail specimens on both test track and mainline track environment to evaluate full-scale reliability and performance of laser cladded rail steel when subjected to actual train loading conditions. Following the comprehensive reliability study, a portable and modular laser cladding machine design was developed for on-track rail steel clad repair operations. Wear life prediction study for the different track and traffic conditions is of paramount importance in developing effective maintenance procedures. As part of the wear life prediction research, historical wear data is used to analyse rail wear degradation. In this statistical wear-life data analysis, the 2-parameter Weibull distribution model is used for wear-out degradation analysis and prediction which characterise wear out failure response for the rail sections at R300 radius and R500 radius curves. Additionally, Zarembski’s rail service wear life model which correlates wear life and fatigue life is modified and extrapolated to conform with Singapore’s railway system loading requirements where nominal wheel load is between 8 to 16 tons. The experimental method for laser cladding of Stellite 6 premium alloy on R350HT pearlitic grade rail steel is developed. The cladding alloy is pre-selected based on literature study due to its promising wear resistant properties whereas the substrate material is a high carbon steel already employed in the railway tracks at sharp-radius curves of (Radius ≤ 500 m). As part of the detailed material characterisation research, microstructural analysis and hardness properties of the clad, the fusion zone, the heat-affected zone (HAZ), and the rail steel substrate has been studied. XVII To study accelerated testing of rail wear, the laboratory scale ball-on-disc tribometer test setup is used to study the wear behaviour of the clad material in comparison to the rail steel substrate. The wear coefficients for the clad material and rail steel are derived from the wear volume analysis using Archard’s wear model. The experimental characterisation research also involves shear testing and analysis to study the clad/substrate material interface bond which is important for the assessment of delamination. The interface bond strength evaluated, and failure mode analysis demonstrate the presence of strong metallurgical bond between cladding material and rail steel.